BRD4 Phosphorylation Regulates HPV E2-Mediated Viral Transcription, Origin Replication, and Cellular MMP-9 Expression - Shwu-Yuan Wu (Cell Reports, 2016)
Post-translational modification can modulate protein conformation and alter binding partner recruitment within gene regulatory regions. Here, we report that bromodomain-containing protein 4 (BRD4), a transcription co-factor and chromatin regulator, uses a phosphorylation-induced switch mechanism to recruit E2 protein encoded by cancer-associated human papillomavirus (HPV) to viral early gene and cellular matrix metalloproteinase-9 (MMP-9) promoters. Enhanced MMP-9 expression, induced upon keratinocyte differentiation, occurs via BRD4-dependent recruitment of active AP-1 and NF-κB to their target sequences. This is triggered by replacement of AP-1 family members JunB and JunD by c-Jun and by re-localization of NF-κB from the cytoplasm to the nucleus. In addition, BRD4 phosphorylation is critical for E2- and origin-dependent HPV DNA replication. A class of phospho-BRD4-targeting compounds, distinct from the BET bromodomain inhibitors, effectively blocks BRD4 phosphorylation-specific functions in transcription and factor recruitment.